Estéreos pessoais e perda auditiva: percepção pelos adolescentes da exposição sonora e dos cuidados auditivos - Carla Souto Bahillo (2014)
This study aimed to verify the sound habits and knowledge about hearing and not hearing risks related to the use of personal stereos, the impact of these habits and the acquisition of protective attitudes after the implementation of the education program for hearing health "Take care of your hearing: pass this idea ahead! "students in the 6th to 9th grade of elementary school two private schools in the city of Belo Horizonte. It was observed that students of schools adopted more protective attitudes towards noise, considering it something to be avoided, after one year of intervention. The use of personal stereos was the most common habit among young people regardless of sex, and with the insert earphone type. However the male students have greater exposure to sound than females. It was concluded that the program of education hearing "Take care of your hearing: Pass this idea forward" was adequate to the school context, requiring only a few adjustments for the pedagogical design of schools. The inclusion of education in auditva health is relevant and effective in school, since the hearing loss induced by exposure to music are discussed, and through an educational process is an efficient tool to avoid them.